1976
DOI: 10.1001/archneur.1976.00500040054008
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Manifestations of Glomus Tumors in the Head and Neck

Abstract: In 75 patients with glomus tumors in the head and neck region, 57 tumors arose from the jugular bulb region, 11 from the middle ear, and seven from the vagus nerve. Thirty-seven percent (28 patients) had cranial nerve paralysis, and 14.6% (11) had intracranial tumor extension. The jugular foramen syndrome was associated with a 50% (two of four patients) incidence, and hypoglossal nerve paralysis with a 75% (three of four) incidence of posterior fossa tumor invasion. Horner syndrome and labyrinthine destruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…15–19 However, for isolated sporadic glomus tumors, the subungual location is by far the most common (60%–80%). 20–22 Sex also plays a role in tumor location, with a subungual location being more common in women, but with no sex preference noted at other locations.…”
Section: Discussionmentioning
confidence: 99%
“…15–19 However, for isolated sporadic glomus tumors, the subungual location is by far the most common (60%–80%). 20–22 Sex also plays a role in tumor location, with a subungual location being more common in women, but with no sex preference noted at other locations.…”
Section: Discussionmentioning
confidence: 99%
“…Familial VP may have a more aggressive growth pattern than a nonfamilial one [Bradshaw and Jansen, 2005]. Due to the high probability of a familial form of the disease [Spector et al, 1976;Zanoletti and Mazzoni, 2006], a detailed family history has to be obtained. If positive, genetic testing including VHL, RET, NF1, SDHD, SDHB and SDHC genes [Klein et al, 1993] is suggested for the patient and first-degree relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Paraganglioma, also known as glomus tumor, is the most frequent neoplastic cause of pulsatile tinnitus [40, 41]. Most paragangliomas are sporadic, about 7–10% are familial and usually autosomal dominant in inheritance [42].…”
Section: Differential Diagnosis and Imaging Findingsmentioning
confidence: 99%